Optimization of fish sampling procedure for evaluating the specific activity of 137Cs, 90Sr and accumulation coefficients - Yu. V. Khomutinin; V. O. Kashparov; Ukrainian Institute of Agricultural Radiology of NUBiP of Ukraine, Kyiv, Ukraine (Ядерна фізика та енергетика)
Problem of optimization of sampling procedure for evaluating the median of specific activity and accumulation coefficients of the 137Cs and 90Sr for the populations of different species of fish lived in the pond was observed. Estimates of the geometric standard deviation of the specific activity (1.2 ÷ 1.9) and accumulation coefficients (1.8 ÷ 2.3) of radionuclides for different species of fish were obtained. Minimum number of samples required for evaluating the median of the specific activity and corresponding accumulation coefficients of 137Cs and 90Sr with desired relative error was determined. In order to obtain the median value of the specific activity of 137Cs with relative error δ = 20 % and confidence level of p = 0.95 at the time of harvest the following numbers of fish samples should be selected for the activity measurement: 16 - 20 samples of pike, perch, sunder, rudd and grass carp; 10 - 13 samples of catfish, bream, tench, carassius, pelecus cultratus; 8-9 samples of bream, roach, carp (common carp), bighead carp; and 5 samples of chub.